Obesity as a determinant of perioperative and postoperative outcome in patients following colorectal cancer surgery: A population-based study (2009–2016). Issue 12 (December 2018) - Poelemeijer, Youri Q.M.; Lijftogt, Niki; Detering, Robin; Fiocco, Marta; Tollenaar, Rob A.E.M.; Wouters, Michel W.J.M.
Abstract: Background: Obesity is an increasing problem worldwide that can influence perioperative and postoperative outcomes. However, the relationship between obesity and treatment-related perioperative and short-term postoperative morbidity after colorectal resections is still subject to debate. Study: Patients were selected from the DCRA, a population-based audit including 83 hospitals performing colorectal cancer (CRC) surgery. Data regarding primary resections between 2009 and 2016 were eligible for analyses. Patients were subdivided into six categories: underweight, normal weight, overweight and obesity class I, II and III. Results: Of 71, 084 patients, 17.7% with colon and 16.4% with rectal cancer were categorized as obese. Significant differences were found for the 30-day overall postoperative complication rate (p < 0.001), prolonged hospitalization (p < 0.001) and readmission rate (colon cancer p < 0.005; rectal cancer p < 0.002) in obese CRC patients. Multivariate analysis identified BMI ≥30 kg/m 2 as independent predictor of a complicated postoperative course in CRC patients. Furthermore, obesity-related comorbidities were associated with higher postoperative morbidity, prolonged hospitalization and a higher readmission rate. No significant differences in performance were observed in postoperative outcomes of morbidly obese CRC patients between hospitals performing bariatric surgery and hospitals that did not. Conclusion: The real-life data analysed in this study reflect daily practice in the Netherlands and identify obesity as a significant risk factor in CRC patients. Obesity-related comorbidities were associated with higher postoperative morbidity, prolonged hospitalization and a higher readmission rate in obese CRC patients. No differences were observed between hospitals performing bariatric surgery and hospitals that did not.